Ultrastructural and proteomic evidence for the presence of a putative nucleolus in an Archaeon - Islas-Morales, Parsifal F.; Cárdenas, Anny; Mosqueira, María J.; Jiménez-García, Luis Felipe; Voolstra, Christian R. (Frontiers in Microbiology, 2023)
Nucleoli are subcellular compartments where transcription and maturation of pre-ribosomal RNAs occur. While the transcription of ribosomal RNAs is common to all living cells, the presence and ultrastructure of nucleoli has been only documented in eukaryotes. Asgard-Archaea, the closest prokaryotic relatives of eukaryotes, and their near relatives TACK-Archaea have homologs of nucleolar proteins and RNAs in their genome, but the cellular organization of both is largely unexplored. Here we provide ultrastructural and molecular evidence for the presence of putative nucleolus-like subcellular domains in the TACK crenarchaeon Saccharolobus solfataricus (formerly known as Sulfolobus solfataricus). Transmission electron microscopy (TEM) revealed consistent electron-dense fibro-granular compartments, also positive to the specific silver staining for nucleolar organizer regions (AgNOR). TEM also confirmed that ribosomal DNA (rDNA) is spatially distributed in non-random, clustered arrays underlying fine structures, as observed by ultrastructural in situ hybridization (UISH). To further explore these observations, proteomic sequencing of isolated bands from AgNOR-stained protein gels was conducted and compared against a compiled inventory of putative nucleolar homologs from the S. solfataricus P1 genome. Sequenced AgNOR-sensitive peptides encoded homologs of eukaryotic nucleoli proteins, enriched for nucleolus-related functions. Our results provide first evidence that subcellular domains of nucleolar-like nature are not exclusive to eukaryotes. Based on our data, we propose a model for a putative nucleolus in S. solfataricus. Whereas technical limitations and further aspects remain a matter for future functional studies, our data supports the origin of nucleoli within the common ancestor of Eukarya and TACK-Archaea, based on a two-domain tree of life.